Exploring Integrative Ministerial Education in African Theological Institutions - Naidoo, Marilyn ca. 20./21. Jh. (International bulletin of mission research, 2022)
In religious Africa, theological education and ministerial formation are strategically important, as leadership development impacts church practice and supports community well-being and development. In a time of profound fragmentation, the great aspiration of “integration” is seen as a solution to connect and transform ministry training, with little consensus, however, about what the term means. Since African theological education needs to respond to training in innovative ways, this article reports on an African study on integrative theological education. It reveals the institutional and contextual challenges that impinge on educational practice and underlines integration as a key approach to professional education.